Assessment of an intensive education program for pharmacists on treatment of tobacco use disorder using an objective structured clinical examination: a randomized controlled trial - Maguy Saffouh El Hajj; Ahmed Awaisu; Mohamad Haniki Nik Mohamed; Rana Ahmed Saleh; Noora Mohammed Al Hamad; Nadir Kheir; Ziyad R. Mahfoud (BMC Medical Education, 2022)
Abstract Background Tobacco use is one of the major public health threats globally. Community pharmacists are uniquely positioned to offer tobacco cessation services owing to their easy accessibility by the public. To prepare Qatar community pharmacists to develop the competencies and skills required to offer smoking cessation services, an intensive tobacco control education program was designed and implemented. The study aimed to assess the impact of the tobacco education program on the pharmacists’ skills and competence. Methods A random sample of community pharmacists in Qatar was chosen for participation in the program. Consenting participants were randomly assigned to either intervention or control groups. The intervention group received an intensive education program on treatment of tobacco-use disorder, while a short didactic session on a non-tobacco-related topic was delivered to the control group. The pharmacists’ tobacco cessation skills and competencies were assessed using an Objective Structured Clinical Examination (OSCE). Results A total of 54 and 32 community pharmacists in the intervention group and the control group, respectively, completed the OSCE. The intensive tobacco education group achieved significantly higher total scores than the control group in all the OSCE cases. Specifically, the mean total scores for the intervention group were 15.2, 15.3, 14.2, 14.6, 16.3, and 15.2 compared to 8.8, 6.2, 7.7, 9.2, 8.3, and 11.3 for the control group (p < 0.001) for cases one to six respectively. Conclusion The study demonstrated that an intensive tobacco cessation education program can improve pharmacists’ tobacco cessation skills and increase their tobacco cessation counseling abilities. Trial registration Clinical Trials NCT03518476 ( https://clinicaltrials.gov/ct2/show/NCT03518476 ) Registration date: May 8, 2018.